The MultiBac Baculovirus/Insect Cell Expression Vector System for Producing Complex Protein Biologics - Sari, Duygu (Advanced Technologies for Protein Complex Production and Characterization, 2015)
Multiprotein complexes regulate most if not all cellular functions. Elucidating the structure and function of these complex cellular machines is essential for understanding biology. Moreover, multiprotein complexes by themselves constitute powerful reagents as biologics for the prevention and treatment of human diseases. Recombinant production by the baculovirus/insect cell expression system is particularly useful for expressing proteins of eukaryotic origin and their complexes. MultiBac, an advanced baculovirus/insect cell system, has been widely adopted in the last decade to produce multiprotein complexes with many subunits that were hitherto inaccessible, for academic and industrial research and development. The MultiBac system, its development and numerous applications are presented. Future opportunities for utilizing MultiBac to catalyze discovery are outlined.